(untitled) (International Seven Journal of Multidisciplinary, 2026)
Persistent Depressive Disorder (PDD), previously known as dysthymia, is characterized by a chronic, progressive, and often treatment-resistant course, associated with significant functional impairment and continuous reduction in quality of life. This study aimed to analyze contemporary therapeutic strategies for the management of dysthymia, with an emphasis on long-term approaches and factors associated with clinical and functional remission. It is a literature review conducted through searches in PubMed and the Virtual Health Library, covering studies published in the last five years, focusing on pharmacological, psychotherapeutic, neurobiological, and technological interventions related to PDD. The analyzed studies highlight that PDD involves neurobiological alterations in subcortical structures associated with motivation and the reward system, contributing to its chronicity and limited response to conventional antidepressants. In pharmacological management, favorable evidence has been observed for the use of bupropion, lamotrigine, and, in treatment-resistant cases, amantadine, indicating promising therapeutic alternatives. The combination of pharmacotherapy and psychotherapy, especially Cognitive-Behavioral Therapy, has demonstrated greater efficacy in reducing symptoms and preventing relapses. Furthermore, psychological interventions based on digital technology showed a positive impact on quality of life improvement and ongoing treatment support. It is concluded that the management of Persistent Depressive Disorder requires an integrated, longitudinal, and individualized approach that considers the neurobiological, psychosocial, and clinical aspects involved in the chronification of the disorder. The combination of targeted pharmacological interventions, structured psychotherapy, and digital technologies constitutes a relevant strategy to promote clinical stability, sustained remission, and reduction of the functional impact of PDD.